2012
DOI: 10.1128/jvi.00595-12
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Replication and APOBEC3 Antiviral Activity Are Not Regulated by P Bodies

Abstract: The APOBEC3 cytidine deaminases play a critical role in host-mediated defense against exogenous viruses, most notably, human immunodeficiency virus type-1 (HIV-1) and endogenous transposable elements. APOBEC3G and APOBEC3F interact with numerous proteins that regulate cellular RNA metabolism, including components of the RNA-induced silencing complex (RISC), and colocalize with a subset of these proteins to mRNA processing bodies (P bodies), which are sites of mRNA translational repression and decay. We sought … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 110 publications
7
45
1
Order By: Relevance
“…The results indicated that inhibiting RISC function The copy numbers of HIV-1 gag RNA in the presence or absence of FLAG-Mov10 were adjusted for RNA input by determination of cellular ␤-actin RNA copy had no effect on Mov10 virion incorporation. As expected from previous studies (30,59), AGO2 knockdown alone increased virus infectivity approximately 2.5-fold; however, AGO2 knockdown did not significantly influence the ability of Mov10 or A3G to inhibit virus infectivity (Fig. 8F).…”
Section: Mov10supporting
confidence: 67%
See 1 more Smart Citation
“…The results indicated that inhibiting RISC function The copy numbers of HIV-1 gag RNA in the presence or absence of FLAG-Mov10 were adjusted for RNA input by determination of cellular ␤-actin RNA copy had no effect on Mov10 virion incorporation. As expected from previous studies (30,59), AGO2 knockdown alone increased virus infectivity approximately 2.5-fold; however, AGO2 knockdown did not significantly influence the ability of Mov10 or A3G to inhibit virus infectivity (Fig. 8F).…”
Section: Mov10supporting
confidence: 67%
“…We further investigated the role of P bodies in Mov10 virion incorporation and antiviral activity by siRNA knockdown of DDX6, which has been shown to deplete microscopically visible P bodies (57)(58)(59). Transfection of HeLa cells with the DDX6 siRNA, but not control siRNA, resulted in substantial reduction in the number of P bodies, as determined by the detection of cytoplasmic granules containing eYFP-Mov10 or eYFP-V866A (Fig.…”
Section: Mov10mentioning
confidence: 99%
“…First, RNA editing is a bona fide function for at least two family members, APOBEC1 (Teng et al, 1993) and A3A (Sharma et al, 2015). Second, RNA has been implicated in governing the cytoplasmic localization of A3G and A3F, including accumulation in stress granules and RNA processing bodies (Gallois-Montbrun et al, 2007; Izumi et al, 2013; Kozak et al, 2006; Phalora et al, 2012; Stenglein et al, 2008; Wichroski et al, 2006). Third, an RNA-dependent interaction is required for A3G and A3F to interact with HIV-1 Gag, gain access to assembling viral particles, and exert antiviral activity (Apolonia et al, 2015; Bogerd and Cullen, 2008; Cen et al, 2004; Huthoff and Malim, 2007; Khan et al, 2005; Schafer et al, 2004; Svarovskaia et al, 2004; Wang et al, 2007; Wang et al, 2008; York et al, 2016; Zennou et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…APOBEC3F and 3G localize to PBs as well as SGs (Wichroski et al, 2006;Gallois-Montbrun et al, 2007) where they interact with different proteins, including the RISC protein (Ago2), PB proteins, (Dcp1 and Dcp2) and PB-SG protein (DDX6) (Kozak et al, 2006). Although discrepancies exist with regard to interactions among various PB constituents and HIV-1 RNA, mRNA, and Gag proteins (Nathans et al, 2009;Yu et al, 2011;Bouttier et al, 2012;Phalora et al, 2012;Reed et al, 2012), the majority of the studies show that many PB components suppress HIV-1 replication by multiple mechanisms. Similar to APOBEC3, Mov10, an RNA helicase, is incorporated into HIV-1 particles.…”
Section: Pb Constituents That Suppress Virus Replicationmentioning
confidence: 99%